Religious Values, Profit, and Perceived Risk: Understanding Muslim Investor Preference in Female-Centered P2P Lending - Yuridistya Primadhita; Jaenal Effendi; Yeti Lis Purnamadewi; Muhammad Firdaus (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study investigates the influence of religious values, profit orientation, and perceived risk on Muslim investor preferences in female-centered peer-to-peer (P2P) lending. It is situated at the nexus of Islamic finance, gender-focused fintech, and behavioral economics. The analysis underscores the increasing participation of investors in digital financial platforms that cater specifically to female borrowers. A quantitative method is applied, employing Structural Equation Modeling–Partial Least Squares (SEM–PLS) to analyze data collected from 212 respondents. The results indicate that religious values, profit orientation, and perceived risk significantly shape Muslim investor preferences. Among these factors, perceived risk exerts the strongest influence, followed by religious values and profit orientation. These findings suggest that perceived risk plays a dominant role in investment decision-making, even within frameworks guided by religious principles. This study contributes to the literature by integrating religious, economic, and behavioral perspectives to advance the understanding of investor preferences in Sharia-compliant financial innovations. The results highlight the importance for fintech platforms to align strategic design with investor perceptions of risk and religious adherence to foster greater engagement in female-centered P2P lending.